2021
DOI: 10.1111/myc.13394
|View full text |Cite
|
Sign up to set email alerts
|

A thermal adaptation landscape related to virulence in Mucor irregularis transcriptional profiles

Abstract: The incidence rate of mucormycosis, one deep fungal disease caused by Mucorales, has rapidly increased over recent years. A multi-centre retrospective observational study on adult non-Aspergillus infections from 2004 to 2012 had reported that Mucorales has become the second most common mould pathogens after Aspergillus. 1 One recent statistical analysis of 851 mucormycosis cases from 2000 to 2017 exhibited that Mucorales spp. accounted for 14% (63/447) of the causative pathogens, in which about 8% (5/63) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A recent study investigating the thermal adaptation of Mucor irregularis , once more, demonstrated that strains growing well in high temperature also cause higher mortality rates in infected larvae, which was underlined by higher fungal burden determined by fluorescent staining of homogenized dead larvae ( Zhang et al., 2022 ). Deciphering virulence traits on a genetic level has been delayed in Mucorales due to unavailability of annotated genome sequences and their reluctance to genetic modification.…”
Section: Invertebrate Modelsmentioning
confidence: 99%
“…A recent study investigating the thermal adaptation of Mucor irregularis , once more, demonstrated that strains growing well in high temperature also cause higher mortality rates in infected larvae, which was underlined by higher fungal burden determined by fluorescent staining of homogenized dead larvae ( Zhang et al., 2022 ). Deciphering virulence traits on a genetic level has been delayed in Mucorales due to unavailability of annotated genome sequences and their reluctance to genetic modification.…”
Section: Invertebrate Modelsmentioning
confidence: 99%